Using songs to promote the affective domain in learning listening of EFL students - Melisa, Melisa; Silviyanti, Tgk Maya; Syamaun, Arifin (Universitas Islam Negeri Banda Aceh, 2022)
This qualitative study principally aimed to discover how songs can be used to promote students' affective domain in listening class activities. One English teacher and twenty-five 8th-grade students of a public junior high school in Greater Aceh, Indonesia, were involved in this study. The data were collected through classroom observation. This present study followed Krathwohl, Bloom, and Masia’s (1973) five observation criteria of the affective domain framework. Subsequently, the teacher and four selected students were interviewed for additional data. The results demonstrated that songs have a positive impact on students' affective domain. Students become enthusiastic about learning listening skills. They listened well and remembered the title of the new song (receiving phenomenon); actively participated in the classroom activities (responding phenomenon); demonstrated their problem-solving ability by working together (valuing); and effective time management (organization). Despite their ability to cooperate in group activities, they had no self-reliance when working individually (internalizing values). However, the students agree that the classroom environment was more comfortable and enjoyable. The results of the study suggest that teachers should consider using songs to not only teaches the knowledge but also the culture associated with the song itself when it comes to teaching listening. Aside from the cognitive aspects, teachers should also maintain and track students' progress in the affective domain.